Impact of irrigation and nitrogen levels on bulb yield, nitrogen uptake and water use value of shallot (Allium cepa var. ascalonicum Baker) (International Journal of Irrigation and Water Management, 2014)
A field experiment was carried out at Bahirdar, Northwest Ethiopia, during the dry season of 2009 to evaluate the effects of irrigation levels and nitrogen (N) rates fertilizer on bulb yield, N uptake and water use efficiency (WUE) of shallot. The treatments comprised of three irrigation levels (120, 100, and 50% ETc) and four N rates (0, 59, 105 and 151 kg N ha-1 ) which were laid out in a split-plot design using irrigation levels as a main plot and N levels as a subplot with three replications. Data on plant height, number of leaves, WUE, N uptake, bulb number, average bulb diameter, marketable and unmarketable bulb yields were collected and analyzed. The result showed that irrigation and N levels significantly affected all these parameters. The interaction of irrigation and N also highly significantly affected all these parameters except the number of bulbs and N uptake of shallot. The regression equations (TMBY = 5.67 + 0.022Irr + 0.02N and TBY = 3.12 + 0.02109 Irr + 0.0158 N) revealed that an increase in the amount of irrigation by 1 mm can increase marketable and total bulb yield by about 0.022 and 0.0209 t ha-1 , respectively and an increase in N by 1 kg ha - 1 can increase the marketable and total bulb yields by 0.022 and 0.0158 t ha-1 , respectively. Application of water at 120% ETc and fertilized with either 105 or 151 kg N ha-1 was the best for maximum marketable (11.64 and 12.03 t ha-1 ) and total bulb yields (12.91 and 13.3 t ha-1 ). From WUE point of view, application of water at 100% ETc and fertilized with 151 kg N ha-1 could be the best practice. However, the yield at this interaction level is significantly lower than the maximum yields. The highest total N uptake (37.18 kg ha-1 ) was obtained at 151 kg N ha-1 .